2014
DOI: 10.2478/s13386-013-0148-z
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of thermoluminescence glow curves in feldspar: evidence for a continuous distribution of energies

Abstract: Abstract:The thermoluminescence (TL) glow curves from feldspars have been the subject of numerous studies, because of their importance in luminescence dating and dosimetry. This paper presents new experimental TL glow curves in a plagioclase feldspar, measured using the T max -T stop technique of glow curve analysis. Kinetic analysis of the experimental results is carried out for a freshly irradiated sample, as well as for a sample which has undergone optical treatment using infrared light for 100 s at 50°C. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…There might be a trap, around ~ 0.3 eV and 0.78 ± 0.09 eV. This is similar to observations reported by Kirsh et al (1987) and Pagonis et al (2014), by measuring the red TL emission of microcline.…”
Section: Put Figure 4 Here (Single Column)supporting
confidence: 84%
“…There might be a trap, around ~ 0.3 eV and 0.78 ± 0.09 eV. This is similar to observations reported by Kirsh et al (1987) and Pagonis et al (2014), by measuring the red TL emission of microcline.…”
Section: Put Figure 4 Here (Single Column)supporting
confidence: 84%
“…Sfamba et al [32] analyzed isothermal luminescence signals from Durango apatite, and found that these signals could be fitted very accurately with the model of Jain et al [22]. Also Pagonis et al [33, submitted] analyzed experimental CW-IRSL curves from 24 different types of feldspars by using the analytical equation (8) Pagonis et al [34] analyzed TL glow curves from feldspar using the model of Jain et al [22], as well as using the general order kinetics model of TL.…”
Section: Discussionmentioning
confidence: 97%
“…The process is then repeated several times by irradiating the same aliquot with the same dose and heating to a slightly higher temperature T stop each time, in steps of 10°C for the complete interval T stop =50-380 o C. This procedure produces a series of TL glow curves which were analyzed in Pagonis et al [34], as well as a series of CW-IRSL curves which are the subject of the study in this paper. Figure 3a shows the result of fitting a typical CW-IRSL curve from sample FL3 (measured at 50 o C) using equation (8).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations